An An Intention to Visit Sharia Tourism in Banten; An Effect of Halal Knowledge and Awareness - Abdul Aziz; Najmudin Najmudin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine (1). The influence of halal knowledge on the intention of tourists to visit Sharia tourist objects in Banten. (2). The influence of halal awareness on the intention of tourists to visit sharia tourism objects in Banten, and (3). The influence of halal knowledge and awareness on the intention of tourists to visit Sharia tourism objects in Banten. The object of this research is tourists who have visited Sharia tourism objects in Banten. The number of samples in this study was set at 120 respondents. The research method used is quantitative. Data collection techniques using a questionnaire. Data were analyzed using multiple linear regression methods through SPSS software version 23. The results of this study indicate that (1). Halal knowledge has a significant positive effect on the intention of tourists to visit Sharia tourist objects in Banten. (2). Halal awareness has a positive and significant effect on the intention of tourists to visit sharia tourism objects in Banten, and (3). Knowledge and awareness of halal have a positive and significant effect on the intention of tourists to visit Sharia tourism objects in Banten. The total contribution of the influence of halal knowledge and awareness on the intention to visit sharia tourism in Banten is 48.3 percent, while the rest is influenced by other variables not examined in this study. Knowledge and awareness of halal have a positive and significant effect on the intention of tourists to visit Sharia tourism objects in Banten. The total contribution of the influence of halal knowledge and awareness on the intention to visit sharia tourism in Banten is 48.3 percent, while the rest is influenced by other variables not examined in this study. Knowledge and awareness of halal have a positive and significant effect on the intention of tourists to visit Sharia tourism objects in Banten. The total contribution of the influence of halal knowledge and awareness on the intention to visit sharia tourism in Banten is 48.3 percent, while the rest is influenced by other variables not examined in this study.